Vastus Lateralis Muscle Free Flap for Skull Base Osteoradionecrosis in Nasopharyngeal Carcinoma - Vlantis, Alexander C.; Wong, Eddy W.Y.; Chiu, Tor W.; Chan, Jason Y.K. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objectives To describe the first experience with a free vastus lateralis muscle-only flap to be used to cover and protect the exposed skull base and carotid artery from radiotherapy-induced skull base osteoradionecrosis (ORN).Design Retrospective review of a case series.Setting Tertiary academic medical center.Participants Post treatment nasopharyngeal carcinoma patients with skull base ORN.Main Outcome Measures Coverage of the internal carotid artery (ICA).Results Four patients underwent the procedure. Following the procedure, all patients were documented to have adequate viable soft tissue covering their ICA. Topical nasal steroids were prescribed to all patients as florid granulation tissue was noted to occur overlying the muscle flap in the early postoperative period. There were no flap failures. All patients noted an improvement in speech, cacosmia, and nasal crusting. No significant epistaxis occurred following surgery. Choanal stenosis was noted in three patients.Conclusion For skull base ORN resulting from the treatment of nasopharyngeal carcinoma (NPC) with radiotherapy that fails conservative management, an open approach to the nasopharynx, that allows debridement then placement of a vastus lateralis muscle-only free flap for coverage, offers a unique and viable approach to the management of this challenging condition.
Keywords: skull base; nasopharyngeal carcinoma; osteoradionecrosis; vastus lateralis; free flap